2020
DOI: 10.1590/0037-8682-0104-2020
|View full text |Cite
|
Sign up to set email alerts
|

The use of Gene-Xpert MTB RIF in the diagnosis of extrapulmonary tuberculosis in childhood and adolescence

Abstract: Introduction: Gene-Xpert MTB RIF (Xpert) is based on nucleic acid amplification by real-time polymerase chain reaction, which allows for the identification of Mycobacterium tuberculosis and rifampin resistance. We describe the use of Xpert for extrapulmonary tuberculosis (EPTB) in children and adolescents. Methods: A case series of two reference centers in Rio de Janeiro from 2014-2019. Results: The final diagnosis of EPTB was established in 11/36 (31%) patients, with five cases detectable by Xpert. For lymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…Ultra detected 67% (4/6) of the patients with enlarged lymph node TB. This percentage is a little higher than in a previous study (56%; 5/9) carried out in our hospital, although the lymph node TB samples were small in both studies 5 . This finding corroborates the Ultra’s superiority over Xpert in the diagnosis of paucibacillary forms of TB.…”
Section: Resultscontrasting
confidence: 71%
“…Ultra detected 67% (4/6) of the patients with enlarged lymph node TB. This percentage is a little higher than in a previous study (56%; 5/9) carried out in our hospital, although the lymph node TB samples were small in both studies 5 . This finding corroborates the Ultra’s superiority over Xpert in the diagnosis of paucibacillary forms of TB.…”
Section: Resultscontrasting
confidence: 71%
“…Clinical studies have shown that when patients developed tuberculous meningitis, localized hematoma fluid appeared, which led to an abnormal rise in inflammatory-related factors. Inflammatory factors and hematoma secretions can lead to a rapid increase in Gene Xpert MTB/RIF (13,14). In this study, Gene Xpert MTB/ RIF was found to be highly expressed in tuberculous meningitis, and the level of Gene Xpert MTB/RIF increased with the amount of hemorrhage, indicating that Gene Xpert MTB/RIF is closely related to tuberculous meningitis.…”
Section: Comparison Of Ada and Tb-dna In Non-tuberculous Meningitis G...mentioning
confidence: 48%
“…After reviewing the titles and abstracts, 31 articles in total were entered into the full-text screening process. After eliminating 10 articles with noncompliant study populations, 1 article with noncompliant disease types and 12 articles with insufficient data, 8 articles [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] were finally included for full-text review and meta-analysis. The flow of the screening is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…(1) In terms of sample size, Alexander W. Kay included 318 samples, and Young Seok Seo included 277 samples, for a total of 527 samples being considered in the present study. After comparing the publication dates of the included studies, we found that a total of four newly published articles (Mijovic [ 26 ], Gautam [ 27 ], Aurilio [ 28 ], Promsena [ 29 ]) were included in this study, adding 369 samples to the analysis. The larger sample size means that the assessment of the diagnostic accuracy of Xpert is more convincing, and the inclusion of newly published articles is more indicative of the diagnostic accuracy of Xpert over recent time periods.…”
Section: Discussionmentioning
confidence: 99%